A model of integrated calcium looping for CO2 capture and concentrated solar power. (October 2015) - Tregambi, Claudio; Montagnaro, Fabio; Salatino, Piero; Solimene, Roberto
Graphical abstract: Highlights: Calcium looping is coupled with a concentrated solar power system. The thermal energy required in the calciner is supplied by a renewable source. The excess incident power during the daytime is stored as calcined sorbent. The performance is analyzed by model computations, based on population balances. The solar field parameters and the role of the operating conditions are assessed. Abstract: Calcium Looping (CaL) is a promising post-combustion CO2 capture and storage technique. Thermal input to the calciner, which is needed to sustain the endothermicity of sorbent regeneration, is usually accomplished via oxy-combustion of an auxiliary fuel. The idea behind the present study is to couple CaL with a Concentrated Solar Power (CSP) system, so that all the thermal energy required in the calciner is supplied by a renewable source. The integration of a CaL cycle with a CSP system offers several potential technical, economical and environmental advantages, but must cope with the inherently unsteady nature of incident solar power. The cyclic character of incident solar power as compared with steady CaL operation could be managed in different ways. In the present study a simple scheme of integrated CaL-CSP process is suggested, based on storage of the excess incident power during the daytime as calcined sorbent, which is eventually utilized in the CaL loop during the nighttime. A preliminary assessment of the performance of this integrated scheme is accomplished by means of model computations. The model is based on a population balance model on sorbent particles, which takes into account the cyclic operation of the system. The parameters of the solar field and the influence of the main operating parameters (sorbent residence time, sorbent/CO2 inlet molar ratio, fluidization velocity) on carbonation degree and efficiency, on sorbent loss by elutriation, on thermal power demand at the calciner and on thermal power produced in the carbonator have been assessed.